Farmer’s Share Analysis of Manohara Sweet Potatoes Marketing Channel - Hariance, Rika (International Journal of Agricultural Sciences, 2023)
The farmer's share is used to assess the marketing efficiency received by farmers as the leading actors in farming. This study aimed to analyze the value obtained by farmers in the marketing chain of Manohara sweet potatoes. The study was conducted in Nagari Koto Tinggi, Baso District, Agam Regency, using a survey method, and the research respondents were 30 purposively selected farmers, collectors, and retailers determined by the snowball sampling method. The data was taken using an interview guide, which was then analyzed descriptively and quantitatively. The results showed three marketing channels for Manohara sweet potato in Nagari Koto Tinggi, Baso District, Agam Regency. The largest farmer's share received by farmers is in the first marketing channel at 100%, the second highest share is in the second marketing channel at 51.6%, and the lowest is in the third marketing channel at 26.11%. The first was a direct marketing channel between farmers and the potato stick agroindustry. However, the number of agroindustries is still small; thus, to increase the value of the farmer's share, increasing the number and scale of the sweet potato agroindustry is the right solution for farmers to sell their crops to the agroindustry directly, and to achieve the welfare of farmers to overcome poverty at the agricultural level.